TUBERCULOUS MENINGITIS IN PREGNANCY - A RARE CASE REPORT - DR.M.SMITHA,; DR.K.SARASWATHI, (International Journal of Pharma and Bio Sciences, 2014)
Tuberculous meningitis is a rare and most severe form of Tuberculosis that too among immuno suppressed individuals. Pregnancy as such is an immunosupressive state, thus providing more chance for reactivation of latent Tuberculosis. We present a case of 33 years female patient G4P1L1A2 with h/o 7 months of amenorrhea came with complaints of intermittent high grade fever and altered sensorium. After doing all investigations, patient was diagnosed to have Tuberculous meningitis, hence started on ATT .MRI showed mild non obstructing hydrocephalus with periventricular seepage, so antiedema measures were given and External ventricular drainage done. Her general condition drastically improved and she spontaneously went in for labour within a week and delivered an alive, preterm female baby with good apgar. Postnatal EEG was normal.